Exercise capacity in the Bidirectional Glenn physiology: Coupling cardiac index, ventricular function and oxygen extraction ratio. Issue 10 (16th July 2015) - Vallecilla, Carolina; Khiabani, Reza H.; Trusty, Phillip; Sandoval, Néstor; Fogel, Mark; Carlos Briceño, Juan; Yoganathan, Ajit P.
Abstract In Bi-directional Glenn (BDG) physiology, the superior systemic circulation and pulmonary circulation are in series. Consequently, only blood from the superior vena cava is oxygenated in the lungs. Oxygenated blood then travels to the ventricle where it is mixed with blood returning from the lower body. Therefore, incremental changes in oxygen extraction ratio (OER) could compromise exercise tolerance. In this study, the effect of exercise on the hemodynamic and ventricular performance of BDG physiology was investigated using clinical patient data as inputs for a lumped parameter model coupled with oxygenation equations. Changes in cardiac index, Qp/Qs, systemic pressure, oxygen extraction ratio and ventricular/vascular coupling ratio were calculated for three different exercise levels. The patient cohort (n=29) was sub-grouped by age and pulmonary vascular resistance (PVR) at rest. It was observed that the changes in exercise tolerance are significant in both comparisons, but most significant when sub-grouped by PVR at rest. Results showed that patients over 2 years old with high PVR are above or close to the upper tolerable limit of OER (0.32) at baseline. Patients with high PVR at rest had very poor exercise tolerance while patients with low PVR at rest could tolerate low exercise conditions. In general, ventricular function of SV patients is too poor to increase CI and fulfill exercise requirements. The presented mathematical model provides a framework to estimate the hemodynamic performance of BDG patients at different exercise levels according to patient specific data.